Fragmentation in semi-arid and arid landscapes: consequences for human and natural systems - Galvin, K.A.; Reid, Robin S.; Behnke, R.H.; Hobbs, N.T. (Springer, 2008)
Exploring the concept of fragmentation, the ecological processes interrupted by fragmentation, and the social consequences of fragmented landscapes, this book presents a timely synthesis on the effects of fragmentation on arid and semi-arid pastoral systems throughout the world.